Online Certificate Injection System (OCIS) implementation at Digicert's clients : user acceptance / Mohd Saipul Adli Mahayadin - Mahayadin, Mohd Saipul Adli (Faculty of Computer and Mathematical Sciences, 2007)
Acceptance research of system focuses on elements relating to usage, system characteristics and task oriented fiinctions. This research analyses the factors influencing user acceptance of Online Certificate Injection System (OCIS) and uses multivariate analysis to develop a technology acceptance model. Nowadays, internet security becomes crucial issues as there are rampant instances where false impersonations of individuals and websites have occurred online, and the problem appears to be on the rise. The protection upon to this problem can be overcome with the use of Digital Certificate which is using a cryptographic system. To implement this certificate, OCIS was developed by Digicert Sdn.Bhd to request the certificate from CCM server and then inject the certificate into the smart card. The smart card contains two certificate. Digital Signature certificate and Non repudiation certificate and can be used to make a secured online transaction. There is a need to understand the users' perspective and their acceptance of OCIS System. Technology acceptance model (TAM) was used as a theoretical basis to understand individual acceptance of users. In this study, five external variables are used to explore individual user acceptance of an OCIS system. It also identifies perceived ease-of-use and perceived usefulness which in turn have a significant effect on individual user acceptance